On the taxonomic status of Gegeneophis nadkarnii Bhatta & Prashanth, 2004 (Amphibia: Gymnophiona: Indotyphlidae) - Gower, David J.; Giri, Varad; Torsekar, Varun R.; Gaikwad, Kshamata; Wilkinson, Mark (Zootaxa, 2013)
Examination of type material and new collections from Goa, southern Maharashtra and northern Karnataka, leads to the conclusion that Gegeneophis nadkarnii Bhatta & Prashanth, 2004 is a subjective junior synonym of Gegeneophis danieli Giri, Wilkinson & Gower, 2003. The purported differences between these species are very minor and attributable to nor-mal individual variation, except for some features of the dentition that are peculiar to the exceptionally abnormal paratype of G. nadkarnii. This taxonomic revision extends the known geographic range of G. danieli and suggests it could be trans-ferred from Data Deficient to Least Concern status in the IUCN Red List.